2021
DOI: 10.1371/journal.pbio.3001275
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic connectivity reveals functionally distinct cortico-hippocampal networks in the human brain

Abstract: Episodic memory depends on interactions between the hippocampus and interconnected neocortical regions. Here, using data-driven analyses of resting-state functional magnetic resonance imaging (fMRI) data, we identified the networks that interact with the hippocampus—the default mode network (DMN) and a “medial temporal network” (MTN) that included regions in the medial temporal lobe (MTL) and precuneus. We observed that the MTN plays a critical role in connecting the visual network to the DMN and hippocampus. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
74
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 143 publications
(277 reference statements)
6
74
2
Order By: Relevance
“…Our results support the presence of dissociable subnetworks within the PM network (Andrews-Hanna et al, 2010; Barnett et al, 2021; Buckner & DiNicola, 2019; Cooper et al, 2021). Previous studies have shown evidence for highly-related subnetworks during rest (Andrews-Hanna et al, 2010; Barnett et al, 2021) and during movie-watching (Cooper et al, 2021).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our results support the presence of dissociable subnetworks within the PM network (Andrews-Hanna et al, 2010; Barnett et al, 2021; Buckner & DiNicola, 2019; Cooper et al, 2021). Previous studies have shown evidence for highly-related subnetworks during rest (Andrews-Hanna et al, 2010; Barnett et al, 2021) and during movie-watching (Cooper et al, 2021).…”
Section: Discussionsupporting
confidence: 84%
“…For example, Cooper and colleagues (2021) examined the functional connectivity of the PM network regions while participants watched a short movie and, using data-driven community detection, showed that the PM network fractured into ventral and dorsal subnetworks that were differentially engaged during event perception. Barnett and colleagues (2021) used a similar data-driven approach to delineate multiple subnetworks in the PM network using resting-state data while also showing evidence that the regions of the different PM subnetworks represented similar information during a memory-guided decision making task. While these studies provide support for a subnetwork view of the PM network, it currently remains unclear whether these subnetworks are dissociable in their contributions to episodic recollection.…”
mentioning
confidence: 99%
“…It also is possible that the aberrant FC between the rCA3 and the posterior brain regions was more sensitive to VSWM impairment in the rTLE patients. We found SBFC was decreased between the rCA3 and the rPVC, which might suggest the disruption of the MTN in that the MTN was considered to serve as a bridge functionally connecting the visual cortex and the DMN/hippocampus ( 34 ). The impaired functional integration of rPVC, rCA3, and the MTN might impact the interaction between visual information and memory maintenance.…”
Section: Discussionmentioning
confidence: 90%
“…These cognitive processes are highly correlated with VSWM. Moreover, a recent study has analyzed a resting fMRI data of healthy adults with data-driven method and demonstrated that the right posterior hippocampus belongs to a medial temporal network (MTN) (similar to the MTL-DMN defined by Andrews–Hanna) that engages in several processes that are critical for WM, including encoding, familiar perception, recognition, recall, and episodic retrieval ( 34 ). Also, the CA3 subfield, located at the top of the transverse section of the hippocampus, is a unique hippocampal subfield in that it contains numerous recurrent collaterals (also called auto-associative network), which are responsible for spatial associations and memory consolidation ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Capalette et al, (2020) compared activation when an object could be predicted following a visual scene, against trials when the object could not be predicted, finding that the precuneus was more active when predictions could be made, suggesting that the region may play a role in integrating contextual and object details. These posterior regions comprise a posterior medial (PM) network, implicated in processing contextual and episodic details (Ranganath and Ritchey, 2012;Ritchey and Cooper, 2020), which displays connectivity with the posterior hippocampus (Barnett et al, 2021(Barnett et al, , 2019. In contrast, the anterior hippocampus has connectivity with an anterior temporal (AT) network including the perirhinal cortex, temporal pole, amygdala and orbitofrontal cortex, and is thought to represent item and object information, but not contextual details (Ranganath and Ritchey, 2012;Ritchey and Cooper, 2020).…”
Section: Introductionmentioning
confidence: 99%